Hak-Hak Bagi Pelaku Delinkuensi Anak dalam Penegakan Hukum Pidana (Studi Komparasi Undang-Undang Peradilan Anak Nomor 3 Tahun 1997 dengan Konverensi Internasional Tentang Hak-Hak Anak) - Trisno Rahajo (LP3 UMY, 2015)
The society and the slate hove done efrorts to implement the rights of children either at lhe national or internalional level. The efforts are intended to provide children wilh lhe welfare lhey need, such as education, development, protection and rehabilitation. The target is children with problems, i.e. steeFchildten, poor, delinquenl, ond disabled children. The efforts are designaled to enable them to grow and develop normally in their physical, mind, and as well as social life